2021
DOI: 10.1017/s1368980021003517
|View full text |Cite
|
Sign up to set email alerts
|

Potential of existing online 24-h dietary recall tools for national dietary surveys

Abstract: Objective: To describe existing online 24-hour dietary recall (24hDR) tools in terms of functionalities and ability to tackle challenges encountered during national dietary surveys, such as maximizing response rates and collecting high-quality data from a representative sample of the population, while minimizing the cost and response burden. Design: A search (from 2000 to 2019) was conducted in peer-reviewed and grey literature. For each tool, information on functionalities, validation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 103 publications
2
23
1
Order By: Relevance
“…Similar to the picture seen in other national surveys, 51 NDNS RP response rates have declined in recent years. An internal review in 2018 found no substantive evidence linking the decrease in response rates to a possible increase in bias of NDNS RP estimates.…”
Section: Strengths and Weaknessessupporting
confidence: 83%
“…Similar to the picture seen in other national surveys, 51 NDNS RP response rates have declined in recent years. An internal review in 2018 found no substantive evidence linking the decrease in response rates to a possible increase in bias of NDNS RP estimates.…”
Section: Strengths and Weaknessessupporting
confidence: 83%
“…A previous study showed that replication rates of a second 24HR greater than 40% did not lead to significant impairment in precision, and that impairment was reduced when the sample was increased, suggesting that choosing an appropriate replication rate to estimate dietary intake may help reduce costs [35]. There are many studies demonstrating the feasibility of online 24-h reviews, and their use can also reduce survey costs and subject burden [36,37]. The vehicles for implementing the 24HR method are diverse and can be used flexibly in actual investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Usability was assessed using the SUS administered after experiencing each recall tools. The SUS is one of the most common questionnaires used to evaluate a variety of softwares including in the field of nutrition [ 7 , 15 ]. The SUS score of the R24W was 23 points higher than the SUS score of the ASA24-Canada-2018.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that broadening the food database would likely increase usability for both the R24W and the ASA24-Canada-2018. According to a recent literature review, the ability to easily identify the correct food is one of the most common issues raised in web-based 24-h recall tools usability studies [ 7 ]. In the next few years, the integration of more branded products into these tools should be considered to facilitate the identification of the exact food consumed while providing many descriptors (e.g., country of origin and presence of nutrition or health claim) with less data management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation